School counselors’ understanding and implementation of Rational Emotive Behavior Therapy (REBT)-based individual counseling in junior high schools in Yogyakarta City: A preliminary study for REBT e-module development - Meri Indryani; Nanang Erma Gunawan (ProGCouns: Journal of Professionals in Guidance and Counseling, 2025)
This study aimed to examine school counselors’ understanding and competence in implementing Rational Emotive Behavior Therapy (REBT)-based individual counseling in public junior high schools in Yogyakarta City as a needs assessment within a research and development framework. A mixed-methods design with a descriptive approach was employed. Twenty school counselors were selected through purposive sampling. Data were collected using a knowledge assessment test, a needs assessment questionnaire, and structured interviews. Instrument validity was established through expert judgment, while reliability was assessed using Cronbach’s Alpha. Data were analyzed using descriptive statistics and thematic analysis. The findings revealed that school counselors demonstrated a moderate level of understanding of REBT concepts. Although most participants were familiar with the fundamental principles of REBT, their practical competence remained limited, particularly in applying the ABC model, identifying irrational beliefs, and implementing disputation techniques. The interview findings further indicated that counseling practices were often based on intuition and personal experience rather than on a systematic theoretical framework. These results highlight a gap between counselors’ conceptual knowledge and practical counseling skills. The needs assessment provides empirical support for the development of a practical and contextually relevant REBT-based electronic module (e-module) to enhance counselors’ professional competencies. This need was reinforced by participants’ strong interest in REBT, with 90% expressing willingness to learn more about the approach and 100% indicating readiness to use an REBT-based e-module. Future studies are recommended to develop and evaluate the effectiveness of the proposed e-module through experimental or quasi-experimental research designs